Best Practices for Mapping Replication Origins in Eukaryotic Chromosomes. Issue 1 (2nd September 2014) - Besnard, Emilie; Desprat, Romain; Ryan, Michael; Kahli, Malik; Aladjem, Mirit I.; Lemaitre, Jean‐Marc
Abstract: Understanding the regulatory principles ensuring complete DNA replication in each cell division is critical for deciphering the mechanisms that maintain genomic stability. Recent advances in genome sequencing technology facilitated complete mapping of DNA replication sites and helped move the field from observing replication patterns at a handful of single loci to analyzing replication patterns genome‐wide. These advances address issues, such as the relationship between replication initiation events, transcription, and chromatin modifications, and identify potential replication origin consensus sequences. This unit summarizes the technological and fundamental aspects of replication profiling and briefly discusses novel insights emerging from mining large datasets, published in the last 3 years, and also describes DNA replication dynamics on a whole‐genome scale. Curr. Protoc. Cell Biol . 64:22.18.1‐22.18.13. © 2014 by John Wiley & Sons, Inc.